English Students' Effort to Face Online Learning Challenges - Sheren Novitasari Setio; Ria Angraini; Kiagus Baluqiah; Yupika Maryansyah (Literary Criticism, 2022)
AbstractThe students do online learning covid-19 pandemic, which makes them study remotely at home, where before the pandemic they did face-to-face learning. The pandemic brings many challenges for students that require students to try to get past the challenges of distance learning. This research was conducted to determine the efforts of students to face the challenges of online learning in English Education, Muhammadiyah University of Bengkulu. This research was descriptive qualitative study. This research used a questionnaire as an instrument of the research (Barrot et al, 2021). They were distributed to 107 students of the English Education Study Program at Muhammadiyah University of Bengkulu. The result of the research show that there are some of students’ efforts to face online learning challenges, namely: self-regulation challenges, technological literacy and competency challenges, student isolation challenges, technology adequacy challenges, technological complexity challenges, learning resource challenges, and learning environment challenges. Those seven types of challenges are often done by the students as this effort to face online learning challenges in pandemic Covid-19. Based on the results above, it can be concluded that the of students' efforts in online learning challenges is Technological Complexity. Where the highest result is 44% or 48 students often did that effort to face online learning challenges.Keywords: Students’ Effort, Online Learning, Challenges